HUBUNGAN ANTARA WORK STRESS, WORK LOAD, DAN SELF EFFICACY TERHADAP KINERJA PEGAWAI KANTOR KOMISI PEMILIHAN UMUM KOTA PAGARALAM - Tasya Mulia Sari; Merta Kusuma (UM. Bengkulu, 2026)
This study aims to analyze the relationship between work stress, workload, and self-efficacy on the performance of employees at the Pagaralam City General Election Commission (KPU) office. This research is a quantitative descriptive study, with the population being employees at the Pagaralam City General Election Commission (KPU) office. Data collection techniques used were observation and questionnaires. Data analysis techniques included descriptive analysis, inferential analysis using SPSS, and coefficient of determination (R2) analysis. The results of this study indicate that work stress has no relationship to the performance of employees at the Pagaralam City General Election Commission (KPU) office. This means that the level of work stress experienced by employees is not directly related to their performance. Workload has no relationship to the performance of employees at the Pagaralam City General Election Commission (KPU) office. This means that the workload experienced does not directly affect employee performance. Self-efficacy has a positive relationship to the performance of employees at the Pagaralam City General Election Commission (KPU) office. This indicates that self-efficacy is very important for an employee in carrying out their work. Work stress, I, and self-efficacy simultaneously or together have a positive and significant relationship to employee performance at the Pagaralam City General Election Commission (KPU) office. This means that if the employee's Work Stress, Work Load, and Self-Efficacy are positive, their performance will be better and optimal. Keywords : work stress, work load, self efficacy.